Five-Years Outcomes of Different Procedures for The Treatment of Female Stress Urinary Incontinence: A Systematic Review and Network Meta-Analysis - Doaa Effat (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Introduction:The current body of evidence is limited regarding the long-term outcomes of different modalities for stress urinary incontinence (SUI). We conducted this systematic review and network meta-analysis to compare the long-term follow-up outcomes of mid-urethral slings (MUS), Burch colpo-suspension, pubo-vaginal sling (PVS), anterior colporrhaphy with Kelly’s plication, and laser therapy in the treatment of SUIMethods: In this systematic review and network meta-analysis, we included prospective and retrospective studies that assessed the long-term outcomes of modalities for the management of SUI. We performed an online, bibliographic, search in four bibliographic databases: Cochrane Central Register of Controlled Trials (CENTRAL), Medline via PubMed, Web of Science, and Scopus.Results: A total of 42 studies were included. For the subjective cure rate, five different interventions were compared; pooling direct and indirect comparisons revealed an advantage of tension-free vaginal tape (TVT) intervention over TVT-obturator (TVT-O), laparoscopic Burch colpo-suspension, trans-obturator tape (TOT), and TVT-sling (TVT-S). Concerning objective cure rate, the pooling direct and indirect comparisons showed an obvious advantage of TOT, followed by TVT, and then TVT-O, Burch lap, and TVT-S. For repeated surgery, four different interventions were compared, and the comparisons revealed an advantage of TVT intervention over TVT-O, PVS, and TOT. The comparisons revealed the advantage of TVT and TVT-O over other procedures for lower urinary symptoms and postoperative complications.Conclusion: In conclusion, MUS appears to be the most effective and safe procedure for SUI at long-term follow-up. However, these findings should be interpreted with caution as there is scarcity in the published reports assessing long-term outcomes of other modalities, especially PVS and laser therapy.